Global review of quantitative studies of primary moult of birds using the Underhill-Zucchini moult model - Scott, Tanya; Underhill, Les G. (Frontiers in Bird Science, 2024)
Knowledge about the timing of moult and how it fits into the annual cycle, along with breeding and, in some cases migration, is an important component of understanding the life history of birds. In comparison with breeding and migration, there is a lack of knowledge about the moult of birds. Primary moult can be quantified using models such as the Underhill-Zucchini moult model. Studies that included estimates of primary moult parameters (duration, mean start date and standard deviation of mean start date) obtained using the Underhill-Zucchini moult model were compiled from the literature to generate a moult analysis database. These parameters provide information about the timing of moult, how it fits into the annual cycle and how synchronised moult is in the population. Relationships between the estimated moult parameters and a series of explanatory variables were explored. Critical gaps in our understanding of primary moult were revealed. The available data are taxonomically biased towards Charadriiformes and Passeriformes and there are substantial gaps in coverage across the phylogenetic tree. There are severe biases in the global distribution of moult studies across continents, with Africa having almost half of all applications of the moult model. Latitude emerged as an important explanatory variable but there are latitudinal gaps in the data, especially from the Tropic of Capricorn extending to 40°N and in the far northern and far southern hemispheres. Citizen scientists, both bird ringers and photographers, have a key role to play in helping to fill these data gaps. An emerging pattern in the available data is that the timing of primary moult is more synchronised in populations in far northern and far southern latitudes than in temperate or tropical zones, but more data in the far south is needed to confirm this. Timing of moult shows great variability in the tropics and sub-tropical regions of the southern hemisphere. In species that undertake an annual sequential moult, larger birds take longer to moult than smaller birds, but the allometric relationship is not tight. Migrants appear to be more synchronised in their moult than residents.